EVALUATION OF EFFECTIVE APPROACH FOR IN VITRO MATURATION OF CANINE OOCYTES WITH SEQUENTIAL ADDITION OF HORMONES - BABU, TR; REDDY, KRC; REDDY, KCS; KUMAR, VG; AMIN, R; ARUNAKUMARI, G; TEJA, A (The Indian Journal of Animal Reproduction, 2022)
About 134 canine ovaries were collected after routine ovariohysterectomy and 4,848 cumulus-oocyte complexes (COCs) were retrieved. Out of these, 1,080 good quality COCs were cultured in TCM-199 medium supplemented with 10% estrus bitch serum and incubated in 5% CO2 at 37оC for 96 h. These COCs were matured either without (control) or with sequential addition of gonadotropic and steroidal hormones. After 96 h maturation period, the percent COCs expansion and oocyte maturation rate was better in groups in which hormones were added in maturation medium.
Keywords: Canine; COCs; In vitro maturation; Nuclear maturation; Oocytes